Penerapan Finiste State Machine dan Atreus AI Behavior pada AI Musuh dalam Fighting Game - Jong Jeffrey Wicaksono; Djoni Haryadi Setiabudi; Hans Juwiantho (Jurnal Infra, 2020)
Artificial Intelligence (AI) has already become an important part in game development. AI in game have a diverse job to give a direct experience to player. The lack of strategy in enemy AI inside fighting game can make players less motivated when playing. To solve this problem, AI is made which has variety of cooperate strategy that can make attract player’s motivationGame is developed using Unity3D Engine and using C# programming language. Finite State Machine method is used to develop AI which become player enemy and Atreus AI Behavior is given in order to have variety of strategies. Probability also added in AI decision making in order to make the AI less predictable.The results show that AI can run well using FSM and Atreus Behavior merging. Testing is also carried out on 15 players which have a background as a casual player or above. These 15 players are in charge to try the game. The results show that AI is more difficult to beaten and player is motivated to defeat the AI.